IN-SERVICE TEACHERS' VOICES ON AI UTILIZATION IN EDUCATION - I Gde Putu Agus Pramerta (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2025)
Developing personalized instructional content is critical for satisfying the different needs of students, particularly in the context of education. This study aimed to identify the perspectives of in-service teachers in utilizing Artificial intelligence (AI) in education. It also focuses on Generation Z characteristics. The study uses a mixed-methods approach. There are 20 in-service teachers who participated in surveys and interviews. Regarding the use of AI in the educational setting, the findings revealed that in-service teachers have several significant opinions. The use of AI in education has both benefits and challenges. The employment of AI is causing in-service teachers to become more aware. AI has the ability to provide educational resources and enhance teaching methods. However, there are still barriers like a lack of technological know-how and issues with equity. Consequently, maximizing AI's potential in classroom practice requires ongoing teacher training programs, the development of ethical standards and best practices, equitable access to AI resources, and long-term studies on the effects of AI on learning outcomes.